Cloud to surface lightning activity in the Eastern Mediterranean Sea in the context of marine infrastructure safety - J. Silverman; Y. Yair; C. Price; M. Asfur (Geomatics, Natural Hazards & Risk)
Lightning poses a significant threat to safety at sea and to marine infrastructure. Lightning protection systems are designed to withstand currents <200 kA; however, the theoretical limit of lightning intensity is 2–3 times higher. Lightning bolts with peak currents (PCs) greater than 100 kA, also known as Lightning Superbolts (LSBs) occur predominantly over the oceans, including the Eastern Mediterranean Sea. In this study we analyzed the cloud to sea surface lightning activity in the Israeli Mediterranean Exclusive Economic Zone (IMEEZ) based on two global lightning detection networks and Israeli national detection network. The main findings of this survey indicate that 0.4% (n = 557) of the lightning strikes in the IMEEZ have a PC strength significantly higher than 200 kA with median and average PCs of 248 and 298 ± 122 kA (±1STD), respectively. The spatial distribution of the LSBs in the IMEEZ is relatively homogeneous. Considering that seawater salinization and acidification may increase lightning intensity over the IMEEZ by 25% until 2050, it is clear that the risk to marine infrastructure in the region will increase and appropriate steps should be taken to upgrade their lightning protection systems to withstand a PC of 400 kA, which is one STD above the calculated mean.